2010
DOI: 10.1098/rsta.2010.0061
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear fission: the interplay of science and technology

Abstract: When the UK's Calder Hall nuclear power station was connected to the grid in 1956, the programmes that made this possible involved a powerful combination of basic and applied research. Both the science and the engineering were novel, addressing new and challenging problems. That the last Calder Hall reactor was shut down only in 2003 attests to the success of the work. The strengths of bringing basic science to bear on applications continued to be recognized until the 1980s, when government and management fash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…This is an important phenomenon in possible accident scenarios and is discussed in detail by Stoneham. 41 There is no evidence for such an excitation process in thoria: Creating Th 5þ would require the removal of a core electron and Th 3þ is not stable either in the solid or aqueous phases and, as illustrated by the Frost diagram of thorium ions in solution, would be rapidly oxidised to Th 4þ . 42,43 Therefore, during a severe accident, where pure thoria will be exposed to high temperature and a wide range of oxygen chemical potentials, the melting temperature of ThO 2 will not decrease significantly, as might be the case with UO 2 44 in similar conditions.…”
Section: Heat Capacitymentioning
confidence: 99%
“…This is an important phenomenon in possible accident scenarios and is discussed in detail by Stoneham. 41 There is no evidence for such an excitation process in thoria: Creating Th 5þ would require the removal of a core electron and Th 3þ is not stable either in the solid or aqueous phases and, as illustrated by the Frost diagram of thorium ions in solution, would be rapidly oxidised to Th 4þ . 42,43 Therefore, during a severe accident, where pure thoria will be exposed to high temperature and a wide range of oxygen chemical potentials, the melting temperature of ThO 2 will not decrease significantly, as might be the case with UO 2 44 in similar conditions.…”
Section: Heat Capacitymentioning
confidence: 99%
“…In the sections which follow, we will present illustrative applications of both achievements of and problems posed by modelling of energy materials. We will mainly highlight the work of the present authors and their collaborators and we note that other examples of successful applications can be found elsewhere in this issue, especially in the articles of Islam (2010), Duffy (2010) and Stoneham (2010).…”
Section: Introductionmentioning
confidence: 98%
“…83, issue 7, 1987), which established the basic defect structure of the material including the energies for defect generation and for both cation and anion migration. Simple calculations also showed that there was a relatively low-energy inter-cation charge transfer process (Macinnes & Catlow 1980), which was proposed to be responsible for the high temperature specific heat excess in the materialan important phenomenon in possible accident scenarios as discussed in greater detail by Stoneham (2010) in this issue. Defect processes also play a crucial role in battery and fuel cell materials; closely related is the modelling of intercalation which is of major importance in battery technologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been necessary to develop an understanding of the materials data required to demonstrate safe and economic operation. However, there is not an extensive literature on these lessons learnt, although some specific references exist on the role of scientific understanding [2] or the management of ageing, particularly in light water reactors (LWRs) [3]. Rather, recourse has been made to the extensive experience over the last 10-20 years of materials used in Generation II-IV systems (see appendix 1 (stacks.iop.…”
Section: Introductionmentioning
confidence: 99%